Molecular Engineering of Conjugated Polybenzothiadiazoles for Enhanced Hydrogen Production by Photosynthesis. Issue 32 (15th June 2016) - Yang, Can; Ma, Beatriz Chiyin; Zhang, Linzhu; Lin, Sen; Ghasimi, Saman; Landfester, Katharina; Zhang, Kai A. I.; Wang, Xinchen
Abstract: The search for metal‐free organic photocatalysts for H2 production from water using visible light remains a key challenge. Reported herein is a molecular structural design of pure organic photocatalysts, derived from conjugated polybenzothiadiazoles, for photocatalytic H2 evolution using visible light. By alternating the substitution position of the electron‐withdrawing benzothiadizole unit on the phenyl unit as a comonomer, various polymers with either one‐ or three‐dimensional structures were synthesized and the effect of the molecular structure on their catalytic activity was investigated. Photocatalytic H2 evolution efficiencies up to 116 μmol h −1 were observed by employing the linear polymer based on a phenyl‐benzothiadiazole alternating main chain, with an apparent quantum yield (AQY) of 4.01 % at 420 nm using triethanolamine as the sacrificial agent. Abstract : Bring to light : Conjugated polybenzothiadiazoles were introduced as a new family of organic photocatalysts for H2 evolution from water in the presence of electron donors with visible‐light irradiation. The molecular engineering of the electron‐withdrawing benzothiadiazole unit on the phenyl unit allows the construction of either one‐ or three‐dimensional polybenzothiadiazoles, and the effect of the structure on the photocatalytic H2 evolution activity was investigated.